الإطار المعرفي عند ابن فارس وبروكلمان في فقه اللغة : دراسة تحليلية مقارنة - داوودي، آسو صبحي غزائي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study seeks to define the Frame of Epistemology in Arabic philology through the book “al-Sahabi” written by the linguist Ibn Faris by studying his principles and aims. This study compares between the Arab linguistic heritage and a recent study of German Orientalist Carl Bruecklmann (The philology of Semitic languages). The researcher used the Arabic language in a basic way in his study, comparing it to its sisters using a modern methodology and a new vision that had an impact on modern Arabic linguists. The researcher used the descriptive, analytical and comparative methods. The study concluded with a number of results that can be summed up as follows: This is the first linguistic study, entitled "philology", which established a framework for the Frame of Epistemology in Arabic philology, which began with Ibn Fares in his book “al-Sahabi”. Ibn Fares also took the lead in several fields that dealt with modern linguistics today, The Arab researchers understand it only after the orientalists and Westerners dealt with it, including the study of the language from within, using the same language methods and rules of analysis, which was recently called language branches. The research also showed the great effort of the orientalist Karl Brueckelmann in studying Arabic in a contemporary systematic way and made the comparison between Arabic and her sisters, the island Semitic languages, the basis of the findings. The most important is that the Arabic language is the heir to languages of Semitic origins and is the only language among them that retained the assets of island voices, taking into account, and taking into the consideration some prolonged changes that happened to its letters.